Providing Health Education with Audio Visual Media About Baby Massage on Mother's Knowledge and Attitude At Sumartini Palembang Independent Practice Midwife Year 2025 - Rhipiduri Rivanica; Intan Maida Sari; Khairun Nisa (PT Bukuloka Literasi Bangsa, 2026)
ABSTRACT Baby massage is a form of touch therapy that provides important benefits for children's growth and development, especially in the 0-3 years period as a golden period of development. Although it is known to have significant benefits, maternal knowledge and attitudes towards baby massage are still low and influenced by trust in traditional methods. Audio-visual media as an educational tool has the potential to be effective in increasing mothers' knowledge and attitudes about baby massage. The purpose of this study is to determine the Influence of Health Education on Infant Massage on Mother's Knowledge and Attitude. This type of research is Quasi-Experimental with a One Group Pretest-Postest design, a sample taken using the Non-Random Sampling method, namely Purposive Sampling totaling 30 respondents at the Independent Practice of Midwives Sumartini Palembang. The research instrument used a questionnaire. The results of the analysis of the Wilcoxon Signed Ranks Test test after education on mother's knowledge increased with a p-value of 0.000 < 0.05 and the mother's attitude also increased with a p-value of 0.001 < 0.05. There is an Influence of Health Education About Baby Massage on Mothers' Knowledge and Attitudes at PMB Sumartini Palembang in 2025. Keywords: Knowledge, Attitude, Education, Baby Massage.